Copper-Catalyzed C–N Bond Formation via C–H Functionalization: Facile Synthesis of Multisubstituted Imidazo[1,2-a]pyridines from N-(2-Pyridinyl)enaminones - Cacchi, Sandro; Ciogli, Alessia; Demitri, Nicola; Fabrizi, Giancarlo; Ghirga, Francesca; Goggiamani, Antonella; Iazzetti, Antonia; Lamba, Doriano (Synthesis, 2018)
An efficient, new copper-catalyzed approach to the construction of the multisubstituted imidazo[1,2-a]pyridine skeleton from N-(2-pyridinyl)enaminones has been developed.
Keywords: copper; enaminones; imidazo[1,2-a]pyridines; cyclization; C–N bond formation; C–H functionalization